Selective recovery of salts from a ternary eutectic system in EFC using seeding - Aspeling, Benita Jean (Department of Chemical Engineering, 2020)
Industrial and mining saline streams are often multi-component in nature. Much research within Eutectic Freeze Crystallization (EFC) has focused on the crystallization of ice and single salts from aqueous solutions. However, as a single salt and ice are crystallized, the concentration of the non-crystallizing salt species increase until the system is saturated with more than two species. In such a situation, the sequence and rate of crystallization of each species depends on both the kinetics of crystallization of each salt and the interaction between the different species. Seeding could be employed to control kinetics and thereby achieve selective recovery from multi-supersaturated systems. The aim of this study was therefore to determine the effect of seeding on the yield and purity of the salt product in a system supersaturated with two salts and ice. A eutectic MgSO4-Na2SO4-H2O system was chosen for this study as these salts are prevalent in saline waste streams in South Africa. A continuous 2 ℓ jacketed, scraped and stirred glass crystallizer was seeded with Na2SO4∙10H2O, MgSO4∙11H2O and ice. The initial salt seed loading and initial supersaturation were varied. The operating conditions used were 30 minutes residence time, a coolant temperature of -11°C, and operating temperature of approximately - 5.0 to -5.1°C. An increase in seeding mass was found to increase the yield and proportion of the seeded salt in the salt product due to an increase in salt growth rate. However, in all experiments it was found that MgSO4∙11H2O crystallized out at fractions higher than the eutectic thermodynamic ratio, indicating a higher selectivity towards this salt. Furthermore, the introduction of 30 g of MgSO4∙11H2O seeds produced a pure salt product (above 99.4 wt.% purity) and the highest salt yield. A similar mass of either seeding material resulted in a similar total mass of salt product. This was attributed to MgSO4∙11H2O crystallizing as the majority salt, and therefore its kinetics played a major role in the total salt yield. Initial supersaturation was found to have no significant effect on steady state salt purity and yield. This study showed that multiple steady states exist within this system at the same operating conditions but different initial seeding conditions. Seeding was found to have the potential to engineer the salt purity of the overflow and underflow split fractions by changing the individual salt average particle sizes. Therefore, this study showed that selectivity recovery of one salt is possible in a multi supersaturated system through seed engineering.